Penerapan Text Mining dalam Spam Filtering untuk Aplikasi Chat - Ratniasih, Ni Luh; Sudarma, Made; Gunantara, Nyoman (Majalah Ilmiah Teknologi Elektro; Vol 16 No 3 (2017): (September - December) Majalah Ilmiah Teknologi Elektro, 2017)
The Internet has become something important in the communication development. One communication facilities on the Internet is the Internet relay chat or known as chat. Chat applications in real time is often misused for the purpose of spreading the virus, promotions, and other interests known as spam. Spamming is the sending of unwanted messages by someone who has a chat account. This causes the chat account feel uncomfortable with the condition. Based on these problems this research create a chat application that can filter messages or spam filtering by applying text mining. Spam filtering process can be done in two phases: text pre-processing and analyzing. These two phases are carried out to calculate the weight (W) of connectedness with the word spam messages. Based on the results of tests performed on chat applications by applying text mining to perform filtering on spam messages generate the level of accuracy of 91.41%.
Keywords: Aplikasi Chat, Text Mining, Spam filtering.